A qualitative study into parental mediation of adolescents' internet use. (August 2017) - Symons, Katrien; Ponnet, Koen; Walrave, Michel; Heirman, Wannes
Abstract: The vast majority of studies on parental mediation are quantitative by nature, which leads to a lack of in-depth understanding of how parents define and perform their role as socializing agents in this area. The present study offers new insights into how parental mediation is implemented on a daily basis with regard to adolescents' internet use. Therefore, six focus group interviews with parents of children aged 13 to 17 were performed (in total, 34 participants). Concretely, the study investigated (i) how parents perceive their adolescents' internet use, (ii) how parents define their own role as socializing agents, and (iii) how parents perform internet mediation on a daily basis. The results show that parental mediation is best conceived as a dynamic process that stems from the daily interactions between parents and their adolescent children, rather than as a preconceived set of rules and strategies that are implemented. Open communication and making a connection with the adolescent in terms of his or her internet use are parents' preferred strategies for performing parental mediation. The results have implications in terms of parental mediation research as well as in terms of the support directed at parents of adolescent children. Highlights: Parents' perceived role regarding internet parenting defines what practices are applied. Parents' mediation practices are dynamic and alter in response to the child's internet use. Rule-setting and limiting the internet use are perceived as negative mediation practices. Parents prefer open communication and connecting with their child as mediation strategies.